Detection of group A Streptococcus in tonsils from pediatric patients reveals high rate of asymptomatic streptococcal carriage - Roberts Amity L; Connolly Kristie L; Kirse Daniel J; Evans Adele K; Poehling Katherine A; Peters Timothy R; Reid Sean D (BMC, 2012)
Abstract Background Group A Streptococcus (GAS) causes acute tonsillopharyngitis in children, and approximately 20% of this population are chronic carriers of GAS. Antibacterial therapy has previously been shown to be insufficient at clearing GAS carriage. Bacterial biofilms are a surface-attached bacterial community that is encased in a matrix of extracellular polymeric substances. Biofilms have been shown to provide a protective niche against the immune response and antibiotic treatments, and are often associated with recurrent or chronic bacterial infections. The objective of this study was to test the hypothesis that GAS is present within tonsil tissue at the time of tonsillectomy. Methods Blinded immunofluorescent and histological methods were employed to evaluate palatine tonsils from children undergoing routine tonsillectomy for adenotonsillar hypertrophy or recurrent GAS tonsillopharyngitis. Results Immunofluorescence analysis using anti-GAS antibody was positive in 11/30 (37%) children who had tonsillectomy for adenotonsillar hypertrophy and in 10/30 (33%) children who had tonsillectomy for recurrent GAS pharyngitis. Fluorescent microscopy with anti-GAS and anti-cytokeratin 8 & 18 antibodies revealed GAS was localized to the tonsillar reticulated crypts. Scanning electron microscopy identified 3-dimensional communities of cocci similar in size and morphology to GAS. The characteristics of these communities are similar to GAS biofilms from in vivo animal models. Conclusion Our study revealed the presence of GAS within the tonsillar reticulated crypts of approximately one-third of children who underwent tonsillectomy for either adenotonsillar hypertrophy or recurrent GAS tonsillopharyngitis at the Wake Forest School of Medicine. Trial Registration The tissue collected was normally discarded tissue and no patient identifiers were collected. Thus, no subjects were formally enrolled.